Mitigating Nitrous Oxide Emissions from Agricultural Soils with Biochar: A Scientometric and Visual Analysis - Jingyi Ren; Yixuan Wang; Mengqi Luo; Yuxiang Zhuang; Jixiong Wang; Sen Chai; Jun Liu; Ziqi Zhang; Yakun Li; Peng Chen; Qi Wei (Agronomy)
The application of biochar in agricultural ecosystems has been demonstrated as an effective strategy for addressing climate change. This study conducted bibliometric analysis via CiteSpace to evaluate 989 publications (2010–2024) on biochar’s role in mitigating agricultural soil N2O emissions. Key findings include (i) rapid growth in publications and citations, with Science of the Total Environment leading in output and Soil Biology and Biochemistry in citation impact; (ii) China and the Chinese Academy of Sciences dominate national and institutional contributions, and author networks exhibit multi-tiered collaboration structures with limited overlap between high-productivity and high-impact researchers; (iii) research hotspots prioritize global warming potential, carbon footprint, and biochar’s chemistry property, mineralization, and pyrolysis processes; (iv) and the field evolved through three phases, as follows: initial emphasis on biochar–fertilizer synergies (2010–2015), followed by microbial mechanisms (2016–2020), and recent focus on soil carbon dynamics and multi-greenhouse gas interactions (2021–2024). Future research should address feedstock–pyrolysis coupling mechanisms, soil-specific application thresholds, and biochar–water–fertilizer interfacial interactions to optimize emission reduction, enhance nitrogen efficiency, and support China’s “Dual Carbon” goals. The study has important guiding significance for promoting the theoretical framework of sustainable agriculture and climate-resilient soil management.